Do Nominations Close the Gender Gap in Competition? - John Ifcher; Homa Zarghamee (Institute of Labor Economics (IZA), 2020)
Experiments have demonstrated that men are more willing to compete than women in stereotypically male tasks. We examine whether nominations close this gender gap. For example, are male nominators more willing than female nominators to enter nominees into competitions. Further, we consider the interaction between nominator and nominee gender. For example, do men shy away from entering women into competitions, or do they make them compete too much? We find a gender gap in neither nominators' willingness to enter nominees into competitions, nor in nominees' likelihood to be entered into competitions. Interestingly, male and female nominators willingness to enter nominees into competitions is statistically indistinguishable from women's willingness to enter themselves into competitions. We also find that men are significantly more likely to enter themselves than others into competitions; this suggests that a nominating process that excludes self-nominations could have an equalizing effect on the proportion of men and women who enter competitions. Our results also reinforce the assertion that the gender gap in competitive preferences is driven by the "thrill or fear of performing in a competitive environment (Niederle & Vesterlund, 2007)," as this motivation is absent in decision-making for others.
Keywords: H1; H5; P1; 330; nominations; preference for competition; willingness to compete; gender gap; decision making for others; DMfO